Sleep Disorders in Chronic Liver Disease - De Cruz, Sharon; Espiritu, Joseph Roland D.; Zeidler, Michelle; Wang, Tisha S. (Seminars in Respiratory and Critical Care Medicine, 2012)
Sleep-related complaints and disturbances are increasingly recognized in the setting of chronic liver disease and have recently been shown to be an important prognostic factor in patients with advanced chronic liver disease. This article reviews the literature surrounding sleep disturbances and disorders in a variety of types of chronic liver disease. This includes the association of sleep disturbances with hepatitis C and antiviral therapy, primary biliary cirrhosis, and Wilson disease as well as the circadian rhythm abnormalities present in cirrhosis and hepatic encephalopathy. The association between chronic liver disease, particularly nonalcoholic fatty liver disease, and sleep-disordered breathing is also reviewed in detail.
Keywords: sleep apnea; hepatic cirrhosis; electroencephalogram; polysomnogram; circadian rhythm